MITIGASI BENCANA GUNUNG API LEWOTOBI LAKI-LAKI BERBASIS KEARIFAN LOKAL MASYARAKAT DESA NAWOKOTE DI KECAMATAN WULANGGITANG, KABUPATEN FLORES TIMUR - Mare, Yasinta Gekeng; Angin, Ignasius Suban; Rahmawati, Arfita (Universitas Nusa Cendana, 2021)
This aims of this study were: 1) analyze knowledge from aspect of community understanding in the research area towards disaster mitigation of the Male Lewotobi Volcano based on local wisdom, (2) describe the form of local wisdom of the community in the research area on the mitigation of the male Lewotobi Volcano disaster. This research used descriptive qualitative and quantitative. The population in this study was 1,405 people. The sample size was 93 people, determined used Slovin formula. The samples were spread in zone I and zone II of the male Lewotobi Volcano hazard, so that the sample size in each zone was determined proportionally, zone I was 47 people and zone II was 46 people. The data used are primary data and secondary data. Data was collected by means of interviews, observations, and document studies. The results of the study were as follows. First, the level of knowledge of the community understanding aspects of the research area on the mitigation of the Lewotobi Volcano disaster. Males in 2003 belonged to the category of understanding. Second, the forms of local wisdom of the community in the research area in the mitigation of the male Lewotobi Volcano disaster are (1) sociocultural semiotics, (2) physical semiotics, (3) faunal semiotics, and (4) vegetal semiotics.